The Price of War - Federle, Jonathan; Meier, André; Müller, Gernot J.; Mutschler, Willi; Schularick, Moritz (American Economic Review, 2026)
We assemble a new dataset spanning 150 years and 60 countries to study the economic toll of war. A war of average intensity is associated with an output drop of close to 10 percent in the war-site economy, while consumer prices rise by approximately 20 percent. The capital stock, total factor productivity, and equity returns all decline sharply. The economic ramifications of war are not confined to the war site. The evidence points to adverse economic outcomes in other belligerent and third-party countries if they are exposed to the war site through trade linkages or share a common border. (JEL D74, E23, E32, F43, F51, N40)